Odd-even effects in the structure and stability of azobenzene-substituted alkanethiolates on Au(111) and Ag(111) substrates - Gnatek, Dominika; Schuster, Swen; Ossowski, Jakub; Khan, Musammir; Rysz, Jakub; Krakert, Simone; Terfort, Andreas; Zharnikov, Michael; Cyganik, Piotr (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
Structural properties and stability of the self-assembled monolayers (SAMs) of two prototypical azobenzene-based alkanethiols (C6H5-N═N-C6H4-(CH2)n-SH) on Au(111) and Ag(111) substrates were studied in detail using a combination of complementary experimental techniques. The azobenzene moiety in these films was linked to the thiol headgroup via short aliphatic spacers of variable length, i.e., (CH2)3 or (CH2)4, corresponding to a different parity of n. For both Au(111) and Ag(111) substrates, a pronounced dependence of the packing density and molecular inclination on the parity of n was observed, with a higher packing density (by ∼14%) and smaller inclination (by ∼17°) of the azobenzene moieties for n = odd as compared to n = even on Au(111) and reversed, but somewhat reduced, behavior on Ag(111). This dependence was related to the well-known odd-even effects in molecular assembly on noble metal substrates, reported previously for a variety of oligophenyl-substituted alkanethiolate SAMs and observed now for the azobenzene-substituted monolayers as well, underlining their generality. The structural odd-even behavior was accompanied by odd-even effects in the stability of the substrate-S bond, with the latter effects being directly correlated to the respective structure variation. The above results are of general importance for the design of functional monomolecular films and of a particular significance as a basis for dedicated photoisomerization experiments.